Phylogenetic and sequencing analysis of Chikungunya virus (CHIKV) strains from local Pakistani population - Humaira Aziz Sawal; Saifullah Khan Niazi; Eijaz Ghani; Misbah Noor (Journal of the Pakistan Medical Association, 2021)
Objective: The present study aims to outline the genotype of circulating CHIKV strains in Pakistan and their phylogenetic analysis Methods: The study is being conducted at Armed Forces Institute of Pathology after the approval by Institutional Review Board. The study was conducted during the period of Aug 2016 to Sep 2017. During this period we have got the total 11 suspected Chikungunya samples in our center and out of these 7 were positive. The viral RNA was extracted, amplified and then the purified product was sequenced by using Sanger dideoxy method. Structural Prediction and Analysis was performed by using Phyre2 and then models were visualized in PyMol2.2. Results: In our study total 11 samples were analyzed, in which 7 samples were positive and the amplified product from five samples were later sequenced because these samples were of good quality for sequencing. Phylogenetic tree was constructed. Five sequences generated in our study were aligned with other CHIKV sequences reported from all over the world. Conclusion: The phylogenetic analysis showed that the strains present in Pakistan belong to the ECSA genotype and derived from India and South East Asia. These results help in the better understanding of CHIKV evolution in the world and discovered that how CHIKV originated in Pakistan. Keywords: Chikungunya; glycoprotein E1; glycoprotein E2; Aedes aegypti. Continuous...